Ecosystem-based mangrove conservation strategies and the role of communities for sustainable management - Sitiningrum, Diah Sabatini (Journal of Earth Kingdom, 2025)
​​​Background: Mangrove ecosystems provide essential ecological, economic, and social benefits but face significant degradation from human and natural pressures. This study analyzes ecosystem-based conservation strategies in Muara Gembong District, focusing on integrating conservation with sustainable economic activities. Methods: A qualitative descriptive approach was employed through literature reviews and field observations, examining ecotourism and silvofishery systems, community involvement, and institutional capacity. Findings: Results highlight the importance of community participation in mangrove conservation through ecotourism and silvofishery systems. Key challenges include economic pressures, sectoral conflicts, weak institutional capacity, and limited technology. Collaboration among stakeholders, supported by education and policy reinforcement, is essential for success. Conclusion: A holistic approach combining ecological, social, and economic aspects is vital for sustainable mangrove conservation in Muara Gembong. Novelty/Originality of this article: This study integrates ecological, social, and economic dimensions into a cohesive conservation strategy, emphasizing community participation and collaborative governance.